2005
DOI: 10.1503/cmaj.1032017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of specialist follow-up in outpatients with congestive heart failure

Abstract: ResearchRecherche C ongestive heart failure (CHF) afflicts up to 2% of North American adults and, despite many advances in diagnosis and therapy, still portends a poor prognosis, with 1-year mortality of 30%-50%. [1][2][3][4][5] Although the prognosis of patients with CHF is poor even with optimal management, suboptimal diagnosis, investigation and treatment of heart failure and comorbidities (e.g., coronary artery disease) in community-dwelling patients contributes to poor survival. [6][7][8][9] In previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
102
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(108 citation statements)
references
References 30 publications
3
102
3
Order By: Relevance
“…3 Trial registry with electronic publication of research protocols before inception of each trial 4,5 and Web posting of complete data sets upon publication of the findings are 2 measures that could promote greater comprehensiveness and honesty in the reporting of trials.…”
Section: Ray Chepesiukmentioning
confidence: 99%
“…3 Trial registry with electronic publication of research protocols before inception of each trial 4,5 and Web posting of complete data sets upon publication of the findings are 2 measures that could promote greater comprehensiveness and honesty in the reporting of trials.…”
Section: Ray Chepesiukmentioning
confidence: 99%
“…There is significant variability within clinical trials that demonstrated the efficacy of HFCs as a management strategy for patients with HF, and within clinical practice (7)(8)(9)(10). HFCs have expanded in number (11), but remain a scarce resource; therefore, determining the optimal recall frequency may assist in resource allocation.…”
mentioning
confidence: 99%
“…This entity is the unhappy, but logical final path for a diverse group of cardiovascular conditions dominated by ischemic heart disease and hypertension, but also populated by valvular and cardiomyopathic disorders. It constitutes a major cause of morbidity and mortality, which in its acute form is associated with an annualized mortality of at least 21% and a high rehospitalization rate (1,2). Accordingly, heart failure accounts for not only a large burden to the health care system, but also one that has major economic repercussions; it is now the single largest expense for Medicare in the United States (3).…”
mentioning
confidence: 99%